Organizational culture and its relationship to achieving sustainable development A field study at the municipality of Ain El-Melh - benkihoul, mohamed; allouti, achour (Journal of Social Sciences and Humanities, 2021)
The current study aims to reveal the prevailing organizational culture within the headquarters of the municipality of AinEl-Melhand its relationship to achieving sustainable development, as a field study at the headquarters of the municipality of AinEl-Melhwhere the study community consisted of 144 employees selected in a comprehensive survey method, and users in that descriptive approach, and for the purpose of data collection two measures of variable were modified Organizational culture and the sustainable development variable, and their validity and reliability were confirmed using the SPSS 23 program - and using a set of statistical methods. Where the results of the study showed that there is a correlation between the dimensions of organizational culture represented in (values of justice - values of belonging - values of cooperation - values of respect) individually and collectively and achieving sustainable development